Etnične manjšine v slovenskih množičnih medijih - Makarovič, Matej (Družboslovne razprave, 2006)
The image of minorities in the mass media is a significant issue in modern multi-ethnic societies. In the article, the image of ethnic minorities in some Slovenian printed media and in the media of ethnic minorities is analysed. In Slovenia, one cannot speak about a typical media image of ethnic minorities. Minorities appear in the media in the context of various publicly presented topics which are connected with them in a way that cannot be separated from a specific minority or minorities. Consequently, minorities usually find themselves in two different situations in the context of their media representation. In the first case, they have no problems with the quantity of media attention (Roma, non-autochthonous minorities from ex-Yugoslavia) yet they are mentioned in the media especially in conflict situations in which they maybe presented a sacause of the problems. In the case of the Italian and Hungarian minorities, on the other hand, a lack of general media attention can be noticed. A significant role in the media's representation is also played by minority media, which may be encouraged by the state through media polices, and new technologies. The ability to use state benefits or existing technologies largely depends on the strategic competencies of the minorities involved. The state can contribute either to strengthening or eroding such strategic competencies. Intellectual and social capital as elements of strategic competence may increase when they are permanently utilised. In these processes, a significant role can be played by the mass media. Thus, the state can contribute to the creation of either a virtuous circle or a vicious circle of mutual influence.
Keywords: etnične skupine; narodne manjšine; mass media; množični mediji; Slovenia; Slovenija